Gold fever in times of “peace” - dimensions and implications of the gold advancement in Cauca (Colombia) after the Havana Peace Agreement (Abstract) - Hamilton, Dorothea (2019)
The signing of peace agreement in Colombia between the FARC (Revolutionary Armed Forces ofColombia) and the Colombian government, ended the armed conflict that lasted for more than50 years. After the signing the most urgent challenges are: the control of the territory left by thedisbandment of the FARC and the management of the wealth of natural resources in the respectiveareas. The Cauca department is situated in the country’s southwest and has been one of the mostaffected by the past violence and is considered to be amongst the most complicated regions toimplement peace. Reasons being the high level of inequality, the presence of several armed groups,multiethnicity and its wealth in natural resources, especially gold. Gold has become subject of disputeand conflict in recent years. Both large-scale mining and artisanal, informal, illegal and criminal mininghave fueled conflict by its accelerated spreading due to the risen goldprice. And, while the nationalgovernment seeks to promote development through international investment, locals are many timesopposed to any kind of mining activities. The Principle objective of the article is to investigate on thedimensions of legal and illegal gold mining in the Cauca after the signing of the peace contract andquantify economical, ecological and social dimensions of illegal mining. Among them we emphasizethe spatial relationships between illegal mining and murders of human rights defenders. Although wedo not find a direct relationship between illegal mining and human rights violation in all muncipialities,we show that illegal and legal mining is a threat to peace.